Cardiac index, SvO2 or pCO2 gap may determine benefit from ECMO in cardiogenic shock: post-hoc analysis of the multicenter, randomized ECMO-CS trial - Ostadal, Petr; Vondrakova, Dagmar; Rokyta, Richard; Karasek, Jiri; Kruger, Andreas; Janotka, Marek; Naar, Jan; Smalcova, Jana; Hubatova, Marketa; Hromadka, Milan; Volovar, Stefan; Seyfrydova, Miroslava; et al. (Critical care (London, England), 2025)
BACKGROUND: Immediate initiation of extracorporeal membrane oxygenation (ECMO) has not demonstrated benefit in individuals diagnosed with cardiogenic shock based on the presence of hypotension. The relationship between other hemodynamic or metabolic parameters and clinical outcomes, with or without ECMO, is not fully understood. METHODS: The Extracorporeal Membrane Oxygenation in the Therapy of Cardiogenic Shock (ECMO-CS) trial randomly assigned 117 patients diagnosed with cardiogenic shock to 2 groups: immediate initiation of ECMO or early conservative strategy. The present post-hoc analysis investigated the clinical efficacy of immediate ECMO therapy in subgroups with cardiogenic shock-more specific characteristics: low cardiac index, low venous oxygen saturation (SvO2) and high partial carbon dioxide pressure (pCO2) gap. The primary endpoint for this analysis was 1-year all-cause mortality; the secondary endpoint was a composite of mortality or hemodynamic worsening requiring ECMO. RESULTS: Data regarding cardiac index were available for 58 patients. In the subgroup with cardiac index < 2.2 L/min/m2, immediate ECMO initiation was associated with a reduced risk for all-cause death (hazard ratio [HR] 0.48 [95% confidence interval (CI) 0.23-0.99]; p = 0.049; number needed to treat to prevent one death [NNT] 3.6) and composite of all-cause death or hemodynamic worsening (HR 0.30 [95% CI 0.15-0.65]; p = 0.003). Data regarding pCO2 gap were available for 54 patients and, in the subgroup with pCO2 gap > 0.8 kPa, initiation of ECMO was associated with a lower risk for all-cause death (HR 0.43 [95% CI 0.20-0.91]; p = 0.028; NNT 3.5) and the composite endpoint (HR 0.29 [95% CI 0.13-0.62]; p = 0.001). Finally, data regarding SvO2 were available for 95 patients. In the subgroup with SvO2 < 60%, initiation of ECMO was associated with lower risk for all-cause mortality (HR 0.34 [95% CI 0.17-0.67]; p = 0.002; NNT 2.8) and the composite endpoint (HR 0.28 [95% CI 0.14-0.57]; p < 0.001). CONCLUSIONS: Measurement of cardiac index, pCO2 gap and SvO2 could improve the management of cardiogenic shock. The presence of any of the following criteria - low cardiac index, high pCO2 gap and low SvO2 - may indicate a poor prognosis with conservative therapy and a substantial mortality benefit from mechanical circulatory support. TRIAL REGISTRATION: NCT02301819. Retrospectively registered 26 November 2014.
Keywords: Extracorporeal Membrane Oxygenation; mimotělní membránová oxygenace; Female; Cardiac Output; výsledek terapie; ženské pohlaví; Oxygen Saturation; saturace kyslíkem; Therapy; lidé; Treatment Outcome; Carbon Dioxide; Male; Cardiogenic shock; Aged; Shock, Cardiogenic; oxid uhličitý; Extracorporeal membrane oxygenation; lidé středního věku; kardiogenní šok; senioři; mužské pohlaví; Clinical trial; Middle Aged; minutový srdeční výdej; Humans